2011
DOI: 10.21273/jashs.136.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Chrysanthemum in Response to Supplemental Light Provided by Irregular Light Breaks during the Night

Abstract: Circadian rhythms are believed to be of great importance to plant growth and performance under fluctuating climate conditions. However, it is unclear how plants with a functioning circadian clock will respond to irregular light environments that disturb circadian-regulated parameters related to growth. Chrysanthemum (Chrysanthemum morifolium ‘Coral Charm’) was exposed to supplemental light provided as irregular light breaks during the night, achieved by controlling the light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 38 publications
(50 reference statements)
2
8
1
Order By: Relevance
“…Leaf chlorophyll content decreased with increasing DLI apparently due to thicker leaves. Similar observations were reported on chrysanthemum (Chrysanthemum morifolium) (Kjaer and Ottosen, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…Leaf chlorophyll content decreased with increasing DLI apparently due to thicker leaves. Similar observations were reported on chrysanthemum (Chrysanthemum morifolium) (Kjaer and Ottosen, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…Before extraction, all frozen samples were freeze-dried, weighed, and ground in a mixer mill (MM200; Retsch, Haan, Germany). Carbohydrates were extracted using the method described by Kjaer et al [30]. In brief, 3-7 mg of freeze-dried sample was placed in an Eppendorf tube, and 400 µL of 80% ethanol (96% ethanol/10 mM HEPES = 80:20 (v/v)) was added followed by vortexing.…”
Section: Carbohydrate and Pigments Analysismentioning
confidence: 99%
“…The pellet was prepared for starch analysis as described by Kjaer et al [30]. In brief, 1000 µL of distilled water was added to the Eppendorf tube and vortexed.…”
Section: Carbohydrate and Pigments Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These conditions inferred that the effect of rust infection decrement due to Cladosporium and synthetic fungicide applications could not be clearly seen on stalk length. The chrysanthemum vegetative growth mainly progressed until 30 DAP during long day forcing (Kjaer & Ottosen, 2011). The observation of rust infection on Table 2 indicated that the disease incidence up to 35 DAP was still low in all treatment and predictably had not affected the growth quality seriously.…”
Section: Effect Of Cladosporium Treatments On Flower Qualitymentioning
confidence: 95%